The Impact of Principal Leadership and Teacher Professionalism on Teacher Performance: The Mediating Role of Work Motivation during the COVID-19 Pandemic - Rahayu, Puji; Gani, Abdul Juli Andi; Suryadi, Suryadi (Pascasarjana UM, 2024)
The background to this research is based on the learning process during the Covid-19 pandemic which was carried out at home in order to break the chain of spread of Covid-19. The presence of Covid-19 that has hit the world has caused an uncertain situation. The unpreparedness of all elements, including teachers, in learning is a major obstacle. The change in teaching and learning from face-to-face to online requires readiness from all elements. Therefore, the principal's leadership and teacher professionalism are two factors among other factors that can influence teacher performance during the Covid-19 pandemic. The formulation of the problem in this research is the influence of the principal's leadership on work motivation, the influence of teacher professionalism on work motivation, the influence of the principal's leadership on teacher performance, the influence of teacher professionalism on teacher performance, the influence of work motivation on teacher performance, the influence of the principal's leadership on teacher performance through work motivation, the influence of teacher professionalism on teacher performance through work motivation. This research uses quantitative methods with a descriptive approach. This research uses survey research with a sample size of 73 respondents. The data collection technique uses a questionnaire with a Likert scale. The research variables in this study are the independent variable, namely the principal's leadership which is marked with (X1) and teacher professionalism which is marked with (X2), the dependent variable is teacher performance which is marked with (Z), and the intervening variable, namely work motivation which is marked with ( Y).